Dietary intake in young adults born small or appropriate for gestational age: data from the Haguenau cohort. Issue 7 (29th July 2016) - Matta, Joane; Carette, Claire; Levy Marchal, Claire; Bertrand, Julien; Pétéra, Mélanie; Zins, Marie; Pujos-Guillot, Estelle; Comte, Blandine; Czernichow, Sébastien
Abstract : Objectives: Compare the dietary intake of young adults born small for gestational age (SGA) versus those born appropriate for gestational age (AGA). Design: Cross-sectional analysis. Setting: Data at the 8-year follow-up Haguenau cohort (France). Data from 229 AGA-born adults and 172 SGA-born adults with available dietary information are presented. Methods: Dietary intake was based on a food questionnaire including 19 items. The χ 2 test was run to compare intake between SGA-born and AGA-born individuals. An a priori score was calculated based on the adherence to recommendations from the French Nutrition and Health Program and included 8 components with the lowest value indicating a lower adherence to recommendations. The score was then divided into quartiles. Relative risks and 95% CIs, controlling for age and sex in multivariate analysis, were calculated in order to determine the risk of belonging to the first versus the second to the fourth quartiles in SGA-born and AGA-born individuals. Results: Intakes of SGA-born adults indicated that they consumed more meat, sugar and less fish than AGA-born individuals (all p<0.05). Multivariate analyses with adjustment for age and sex showed that the relative risk of belonging to the first quartile versus the other three quartiles did not disclose any significant difference in SGA-born versus AGA-born participants: RR=0.92 (95% CI 0.65 to 1.30). Conclusions: Aside from the differences found by univariate analyses, no significant differences were obtained in multivariate analyses. Findings suggest that parameters of fetal programming are more associated with the development of metabolic syndrome in adulthood rather than dietary patterns.